Fintech 2022 Trends : The era of F-CUBE “Fast and Furious Fintech” - Dubey, Vivek; Walimbe , Rohit S. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Due to the continued advancement in financial technologies, global businesses and startups have discovered new windows for potential economic gains. Potential investors are on the hunt for opportunities that would match the growth trend in fintech opportunities. Through a cross-sectional survey of different articles and other publications, the current study explores the various sectors in which fintech has discovered applicability. Even the emergency of personalities, most predominantly influencers, artists, content writers and unapologetic financial inclusion (low wage group, black, women, etc) has been traced to the 21st-century fintech breakthrough. An analysis of the pre-and post-pandemic fintech trends is also provided based on thorough qualitative research.